Molecular Characterization of Hydatid Cysts Cases in a Wild Boar and Mule in Turkey - Kesik, Harun Kaya; Çelik, Figen; Kılınç, Şeyma Günyaktı; Karabulut, Burak; Çevik, Aydın; Şimşek, Sami (Galenos Publishing House, 2021)
Objective: Cystic echinococcosis (CE) is a zoonotic infection that affects humans, livestock and wild animals through the larval form of Echinococcus granulosus sensu lato (s.l.). Molecular and taxonomic studies carried out in the recent years accept that Echinococcus granulosus s.l., a complex of 5 cryptic species, causes CE. In this study, we performed morphological and molecular characterisation of cyst isolates obtained from a wild boar and mule naturally infected with hydatid cyst. Methods: After gDNA isolation, the mitochondrial cytochrome oxidase subunit 1 (mt-CO1) gene region was amplified by polymerase chain reaction (PCR) with specific primers. The amplified mt-CO1 PCR products were purified and one-way DNA sequence analysis was performed. Results: Comparison of the partial sequences of mt-CO1 gene from the hydatid cyst isolates with that of reference sequences in GenBank revealed 100% similarity with E. granulosus sensu stricto (G1-G3) sequences. Conclusion: To the best of our knowledge, this is the first study to determine the molecular characterisation of Echinococcus species in a wild boar in Turkey. © 2021, Galenos Publishing House. All rights reserved.
Türkiye’de Bir Yaban Domuzu ile Bir Katırda Hidatid Kist Olgusu ve Moleküler Karakterizasyonu
Keywords: Echinococcus granulosus; genotype; hydatid cyst; mule; PCR; wild boar